THE SOCIO-RELIGIOUS PHILOSOPHY OF SRI CHAITANYA - Dr. Banobrata Aditya (IJRDO - Journal of Social Science and Humanities Research, 2026)
An eminent luminary in the firmament of medieval Bangladesh's life, society, and culture was Sri Chaitanya. Through his influence, an unprecedented mass awakening emerged in the material, spiritual, earthly, religious, and social spheres of life in Bangladesh. By disseminating his doctrine of divine love, Sri Chaitanya united a society fragmented by caste and class distinctions into a single bond of human fellowship. Likewise, he ushered in a new current in Bangladesh through the Bhakti movement, transforming the religious and cultural landscape. To analyse and evaluate the profound and far-reaching influence of Sri Chaitanya, the present study has been undertaken.